Pathophysiology of bronchoconstriction: role of oxidatively damaged DNA repair. Issue 1 (February 2016) - Bacsi, Attila; Pan, Lang; Ba, Xueqing; Boldogh, Istvan
Abstract : Purpose of review: To provide an overview on the present understanding of roles of oxidative DNA damage repair in cell signaling underlying bronchoconstriction common to, but not restricted to various forms of asthma and chronic obstructive pulmonary disease. Recent findings: Bronchoconstriction is a tightening of smooth muscle surrounding the bronchi and bronchioles with consequent wheezing and shortness of breath. Key stimuli include air pollutants, viral infections, allergens, thermal and osmotic changes, and shear stress of mucosal epithelium, triggering a wide range of cellular, vascular, and neural events. Although activation of nerve fibers, the role of G-proteins, protein kinases and Ca ++, and molecular interaction within contracting filaments of muscle are well defined, the overarching mechanisms by which a wide range of stimuli initiate these events are not fully understood. Many, if not all, stimuli increase levels of reactive oxygen species, which are signaling and oxidatively modifying macromolecules, including DNA. The primary reactive oxygen species target in DNA is guanine, and 8-oxoguanine is one of the most abundant base lesions. It is repaired by 8-oxoguanine DNA glycosylase1 during base excision repair processes. The product, free 8-oxo-7, 8-dihydro-2′-deoxyguanosine base, is bound by 8-oxoguanine DNA glycosylase1 with high affinity, and the complex then functions as an activator of small guanosine triphosphatases, triggering pathways for inducing gene expression and contraction of intracellular filaments in mast and smooth muscle cells. Summary: Oxidative DNA damage repair-mediated cell activation signaling result in gene expression that 'primes' the mucosal epithelium and submucosal tissues to generate mediators of airway smooth muscle contractions.